Company Readiness towards e-Procurement Adoption: A Case of Gemilang Trader (Journal of Business Management and Accounting, 2016)
The Malaysian Government has been taking many initiatives to upgrade and enhance the e-Procurement system in Malaysia in order to increase the online transactions adoption and sustain the quality of bidding transactions among suppliers. Based on Malaysian Public Sector Information and Communication Technology (ICT) Strategic Plan (2016-2020), one of the main targets is to increase the online e-Procurement system to above 90% of transactions via online by 2016 onward. The objective of this paper is to explore the readiness towards e-Procurement adoption by Gemilang Trader. The case finding is expected to be of help to further enhance and increase the e-Procurement adoption rate among company’s management and staff. Among the major problems regarding company readiness towards e-Procurement adoption are the lack of financial resources, technical compatibility, lack of staff readiness towards e-procurement complexity and lack of technical competence among employees. Data for this study was collected using interview and survey.